Mobile Application for Incident Reporting - Ignaco, Mary Ann E. (Society of Visual Informatics, 2021)
In the Philippines, reporting an incident always depends on self-reporting to the nearest law enforcer's office or calling a channel using a mobile phone. 911 is the National Emergency hotline to get assistance when an emergency occurs. However, the emergency hotline operated by the Emergency Network Philippines (ENP), cannot retrieve the reporter's location details immediately. Only when the reporters describe the exact location clearly. Yet, many circumstances that the reporters do not know when they are, or sometimes they have imprecise position information. Then, the law enforcers team may not be able to come to the right place efficiently on time.Â The incident reporting application incorporates the three types of incidents, classified as public disturbance, ordinance violation, and crime incident. To report an incident the application will automatically get the latitude and longitude of the mobile user or an option to manually pinned the location on the google map include also the incident type, description, and photos will be sent to the nearest barangay responder officer. The barangay responder officer able to request a backup officer, the rescue emergency unit such as a hospital ambulance or firefighters, or transfer a report to the nearest police station. The system also manages web admin for responder locations and generates statistical reports including charts and graphs.Â The positive feedback of the participants during the evaluation stage signifies that the application was accepted as tested and verified by the evaluation results.